The Role of Financial Markets in Incentivising Corporate Social and Environmental Performance - Lynch, Benjamin (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2022)
The central topic of this thesis is the role played by financial markets in incentivising firms to alter their impact on society through non-market strategies relating to environmental and social performance. The thesis implements a three-paper format with each paper examining how different elements impact the valuation of environmental and social performance by equity markets. Each paper examines aspects of the relationship between these non-market strategies and various measures of firm performance through a contextualised lens. Contextualising the relationship allows for a better understanding of the circumstances under which firms are rewarded for increased environmental and social performance with increased returns, valuations and/or a lower cost of equity capital. The use of Refinitiv (formerly Reuter) s Asset4 ESG data in chapters 2 and 3 and my measure of a firm s industry-relative carbon liability reduction in chapter 4 allows this research to examine the relationship between environmental and social performance, and market-based measures of financial performance using industry-relative measures of performance. The importance of considering industry context through the utilization of an industry-relative measure of environmental and social performance rests on the consideration that if investors believe in an optimal level of environmental and social investment, it is likely to be industry-specific in line with other factors such as cost structures, risk profiles and other financial metrics. I also extend my contextualised analysis to consider how institutional forces in the firm s external environment impact the market valuation of its environmental and social activities, in the third and fourth chapters. The second chapter investigates the cost of equity capital as one of the possible conduits through which firm value may be impacted by changes in a firm s corporate social performance (CSP) due to its possible effect on a firm s perceived risk and the relative size of its investor base. It investigates the impact of a firm s CSP on its implied cost of equity capital when all aspects of CSP are not uniformly, timely and linearly priced by the market (Ding, Ferreira, & Wongchoti, 2016) given the asymmetric information and opacity around CSP (Cho, Lee, & Pfeiffer, 2013) in addition to investors heterogeneous ability and desire to price its complexities. Using an estimate of each firms ex-ante cost of equity derived directly from stock prices and cash flow forecasts and a sample of 21,338 firm-year observations from 50 countries during the period from 2002 to 2017, we find a non-linear and stratified relationship. We find that cost of capital reduces with increasing CSP up to a level, beyond which it starts to increase again, representing a reverse J-shaped relationship. I propose that this occurs as investors with a primary focus on wealth maximization perceive the costs of CSP investment to outweigh the benefits at this level. The presence of an increase in cost of capital for firms with the highest level of CSP performance negates the possibility of an absolute truth about the relationship and highlights that the nature of the alignment between social and economic investment incentives is an important determinant of financial market outcomes. The third chapter examines the relationship between CSP and firm value from a contingency perspective by investigating the possible moderating role of country-level institutions. Combining elements of institutional, stakeholder and resource dependency theory, I theorise and test whether markets take an instrumental view of CSP by placing more value on increased performance in relation to a stakeholder group s interests in the presence of institutional forces which increase their salience. Using a sample of 43,171 firm-year observations from 49 countries during the period from 2002 to 2019, we find strong evidence that CSP is more positively related to firm value in countries with strong political, labour and market institutions. This highlights the importance of the presence of institutions which empower societal and environmental stakeholders if market forces are to play a positive supporting role in moving business towards a more sustainable future. The fourth chapter investigates the EU ETS, a market specifically created with the goal of incentivising firms to increase their environmental performance. Using an event study methodology, it examines the impact of EU ETS verified emissions publications and political events on the market value of 123 publicly traded participating firms during the third phase of its operation (2013-2020). I find that positive firm-specific environmental news is associated with higher returns in the latter years of the EU ETS s third phase (2018-2021) while it had an insignificant impact in earlier years (2014-2017). Furthermore, the impact of institutions on market outcomes is further substantiated by my finding of a significant market reaction to a number of political events relating to the revisions of the system. These findings lend further weight to the argument for considering the relationship between environmental and market-based financial performance through a contextual lens, given the time-variant nature of financial market perceptions of the value relevance of corporate actions by demonstrating the ability of institutions to mould financial market outcomes.
APPROVED
Keywords: Corporate Social Responsibility, Corporate Social Performance, ESG, Cost of Equity, financial performance, Firm Value, Institutional theory, Stakeholder theory, Environmental performance, Emissions Trading, Cap and trade system, European Emissions Trading system, EU ETS